2021
DOI: 10.1039/d1sc04531h
|View full text |Cite
|
Sign up to set email alerts
|

Water-stable hydrazone-linked porous organic cages

Abstract: Although porous organic cages (POCs), particularly imine-linked (C=N) ones, have advanced significantly over the last decades, the reversible nature of imine linkages makes them prone to hydrolysis and structure collapse,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 92 publications
0
37
0
1
Order By: Relevance
“…Figure 2h,i clearly show the absorption peaks in POC, corresponding to OH stretching (3337 cm −1 ), NH bending (1518 cm −1 ), and CO stretching (1676 cm −1 ). [ 42,46 ] When POC was deposited on SnO 2 film, these three peaks were shifted down to 3326, 1499, and 1661 cm −1 , respectively. It is reasonable to speculate that the above downshifts are caused by the interaction between SnO 2 and the specific group of POC.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2h,i clearly show the absorption peaks in POC, corresponding to OH stretching (3337 cm −1 ), NH bending (1518 cm −1 ), and CO stretching (1676 cm −1 ). [ 42,46 ] When POC was deposited on SnO 2 film, these three peaks were shifted down to 3326, 1499, and 1661 cm −1 , respectively. It is reasonable to speculate that the above downshifts are caused by the interaction between SnO 2 and the specific group of POC.…”
Section: Resultsmentioning
confidence: 99%
“…123 Recently, some studies revealed the possible application of POCs for trapping the pollutants in sewage. Yang et al 122 used N,N-dimethylformamide (DMF) as a solvent and introduced different dihydrazide linkers onto the concave-shaped tetraformyl-functionalized C4RACHO scaffold, and the seven obtained types of calix [4]-resorcinarene-based POCs (HPOC-101, 102, 103, 104, 201, 301, and 401) all exhibited an I 3 À adsorption capability in water. Notably, as shown in Fig.…”
Section: Water Desalination and Sewage Purificationmentioning
confidence: 99%
“…(b) Time-dependent adsorption of aqueous I 3 À by hydrazone-linked POCs; inset: the recyclability of HPOC-101 for I 3 À removal. (c) Percentage removal efficiency of different water pollutants (0.1 mM) by HPOC-101 (0.5 mg mL À1) 122.…”
mentioning
confidence: 99%
“…This intrinsic drawback could be overcome by using an α-substituted imine, namely acylhydrazone [ 55 , 56 , 57 , 58 , 59 ]. This more robust dynamic bond has been used in the self-assembly of rings [ 60 , 61 , 62 , 63 , 64 , 65 ], cages [ 66 , 67 , 68 , 69 , 70 ], catenanes [ 37 , 71 , 72 ] as well as knots [ 73 ]. We thus envision that it might be possible to obtain bowl via acylhydrazone condensation.…”
Section: Introductionmentioning
confidence: 99%